Modern clinical manifestations of tick-borne encephalitis in Tomsk region - N. G. Zhoukova; A. V. Lepyokhin; L. V. Loukashova; R. F. Nasyrova; N. V. Ryazantseva; M. R. Karpova; A. P. Zima; M. N. Dobkina (Бюллетень сибирской медицины, 2006)
The article presents the results of clinical and epidemiological investigations of morbidity rate of tick-borne encephalitis (TBE) in Tomsk region in a period of 1944—2005. it is shown that Tomsk region is an active natural focus of TBE, leading among other regions of the Russian Federation in morbidity rate and spreading of the infection. Main features of pathomorphosis of clinical ma- nifestitions of TBE were analysed: prevailing of fever and latent forms was determined, as well as decrese of paralytic and menin- geal forms levels.